Penerapan Konseling Naratif untuk Meningkatkan Self Efficacy Belajar Peserta Didik dalam Mengerjakan Tugas - Saifuddin, Saifuddin; Astuti, Budi; Fahrozin, Muh (EduPsyCouns: Journal of Education, Psychology and Counseling, 2024)
The problems studied in this study are: (1) How does the counseling teacher apply information services in classical guidance related to student time management at DDI Uhailanu Junior High School, Aralle District, Mamasa Regency, (2) What are the supporting factors and inhibiting factors experienced by the counseling teacher in applying information services in classical guidance related to student time management at SMP Negeri 3 Polewali. This type of research is qualitative research that builds meaning based on field data. This qualitative research procedure, produces descriptive data in the form of written or spoken words from people and observable behaviour. Data collection is done by conducting observations, interviews, in-depth and documentation. Data analysis is carried out by giving meaning to the data that has been collected, and from the data conclusions are drawn. The results of observations from the Application of Information Services in Classical Guidance Related to Student Time Management at DDI Uhailanu Junior High School, Aralle District, Mamasa Regency which is applied to students at DDI Uhailanu Junior High School, Aralle District, Mamasa Regency, the first step taken is that every year MGMP is held, where this MGMP is (Subject Teacher Deliberation).in the application of information services in classical guidance related to students, namely: identifying information needs for the subject (learners), determining information material as a service to be delivered, determining the target subject of the service, determining the resource person, preparing procedures, tools and service media.